Anti-damage high-heat-insulation rapid construction composite material and preparation method thereof

By adopting a three-layer structure magnesium phosphate cement-based composite material, combined with optimized formula and process, the problem of the difficulty of existing concrete materials in synergistic improvements in four properties: anti-invasion, anti-explosion, insulation and rapid construction is solved, and efficient performance improvement and rapid construction capabilities are achieved.

CN119912235AActive Publication Date: 2025-05-02SOUTHEAST UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411907828.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-05-02
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

It is difficult for existing concrete materials to achieve synergistic improvements in four properties: anti-invasion, anti-explosion, insulation and rapid construction.

Method used

A three-layer composite material is made of magnesium phosphate cement-based ultra-high performance concrete, the middle layer is magnesium phosphate cement-based foam concrete, and the inner layer is magnesium phosphate cement-based high-strength concrete. Through the optimization of formula and process, the strength, toughness and energy absorption characteristics of the material are improved.

Benefits of technology

It has achieved a coordinated improvement of high anti-invasion, explosion resistance and heat insulation performance, and has the characteristics of rapid construction, which has improved the security and combat effectiveness of military facilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005204825200000121
    Figure BDA0005204825200000121
Patent Text Reader

Abstract

The invention relates to a damage-resistant, high-heat-insulation and rapid-construction composite material and a preparation method thereof.The composite material comprises an outer layer material, a middle layer material and an inner layer material which are sequentially compounded, the outer layer material is made of magnesium phosphate cement-based ultra-high-performance concrete, the middle layer material is made of magnesium phosphate cement-based foam concrete, and the inner layer material is made of magnesium phosphate cement-based foam concrete. And the inner layer is made of magnesium phosphate cement-based high-strength concrete. Compared with the prior art, the material has excellent penetration resistance, explosion resistance and heat insulation performance, in addition, the composite material has the characteristic of rapid setting and hardening, efficient construction of components can be achieved, in addition, the bonding strength among the outer layer, the middle layer and the inner layer of the composite material is high, and complex processes such as splicing and anchoring are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials and relates to a damage-resistant, high-heat-insulating, fast-building composite material and a preparation method thereof. Background Art

[0002] In the modern military field, the improvement of the penetration and explosion resistance of concrete structures is crucial to ensuring the safety of troops and combat effectiveness. First, the penetration resistance ensures that military facilities and equipment can withstand direct attacks from enemy weapons, thereby protecting the safety of command centers, warehouses and troops. This feature not only improves the survivability of equipment, but also increases combat continuity and ensures the smooth progress of combat operations; secondly, explosion resistance is particularly important when facing threats such as bombs and artillery shells. Efficient explosion-proof design can effectively reduce the damage caused by explosion shock waves, thereby reducing the risk of damage to military targets; in addition, environmental conditions such as the open sea place high demands on the thermal conductivity of concrete structures. Effective thermal insulation performance can not only protect the normal operation of equipment in high temperature environments, but also provide combatants with a more comfortable living space; in particular, the rapid construction feature enables engineering structures to be quickly deployed in a short period of time, thereby improving response speed and maneuverability.

[0003] In summary, the improvement of anti-penetration, anti-blast and thermal insulation performance, as well as the rapid construction capability, have formed the core elements of modern military engineering, providing a solid guarantee for achieving an advantageous position on the battlefield. However, existing concrete materials find it difficult to achieve the synergy of the above four properties.

[0004] Magnesium phosphate cement has the characteristics of early strength and rapid hardening. At present, the research on magnesium phosphate cement is mainly focused on the repair of pavements and structures. For example, the slow-setting and high-toughness magnesium phosphate cement road rapid repair material disclosed in Chinese patent CN201911194878.2, etc., but its application in the field of damage-resistant materials and rapid construction has not yet been seen. Summary of the invention

[0005] The purpose of the present invention is to provide a damage-resistant, high-insulation, fast-construction composite material and its preparation method. The composite material includes three layers: the outer layer material is magnesium phosphate cement-based ultra-high performance concrete, which has ultra-high strength and high toughness to ensure the high anti-penetration performance of the composite material; the inner layer material is magnesium phosphate cement-based foamed concrete to ensure the high explosion resistance and high insulation performance of the composite material; the inner layer material is magnesium phosphate cement-based high-strength concrete as a structural layer. In addition, the cementitious material is mainly magnesium phosphate cement, which ensures the rapid construction of the composite material, thereby solving the problem that the existing concrete materials are difficult to coordinate in terms of anti-penetration, anti-explosion, insulation and rapid construction.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] In one aspect, the present invention provides a damage-resistant, high-insulation, fast-construction composite material, which comprises an outer layer material, an intermediate layer material and an inner layer material which are compounded in sequence, wherein the outer layer material is made of magnesium phosphate cement-based ultra-high performance concrete, the intermediate layer material is made of magnesium phosphate cement-based foamed concrete, and the inner layer material is made of magnesium phosphate cement-based high-strength concrete, wherein:

[0008] The magnesium phosphate cement-based ultra-high performance concrete (outer layer material) comprises the following raw material components in parts by weight:

[0009] Dead-burned magnesium oxide 500-1100 parts, potassium dihydrogen phosphate 400-900 parts, borax 9-25 parts, fine beads 110-210 parts, steel fiber 50-220 parts, river sand 1000-2000 parts, water 180-250 parts;

[0010] The magnesium phosphate cement-based foamed concrete (middle layer material) comprises the following raw material components in parts by weight:

[0011] Dead-burned magnesium oxide 500-1100 parts, potassium dihydrogen phosphate 400-900 parts, sodium carbonate 5-50 parts, sodium bicarbonate 5-50 parts, PE fiber 0.5-3 parts, river sand 100-650 parts, water 400-800 parts;

[0012] The magnesium phosphate cement-based high-strength concrete (inner layer material) comprises the following raw material components in parts by weight:

[0013] 500-1100 parts of dead-burned magnesium oxide, 400-900 parts of potassium dihydrogen phosphate, 15-45 parts of borax, 600-1200 parts of river sand, 600-1200 parts of crushed stone, and 300-500 parts of water.

[0014] Furthermore, in the raw material composition ratio of the above-mentioned layers of materials, each component can independently select an end value or any intermediate point value within the above-mentioned limited range. For example, for 500-1100 parts of dead-burned magnesium oxide, its weight ratio can be selected as 500 parts and 1100 parts, or it can be any intermediate point value such as 600 parts, 700 parts, 800 parts, 900 parts, 1000 parts, etc. The same applies to the remaining components.

[0015] Furthermore, the dead-burned magnesium oxide is obtained by melting and calcining magnesite powder at a high temperature above 1500°C.

[0016] Furthermore, the potassium dihydrogen phosphate is chemically pure KH 2 PO 4 ;

[0017] The borax is chemical analysis pure Na 2 B 4 O 710H 2 O;

[0018] The sodium carbonate is chemical analysis pure Na 2 CO 3 ;

[0019] The sodium bicarbonate is chemically pure NaHCO 3 .

[0020] Furthermore, the particle size of the river sand is 0-5 mm, and is not equal to 0.

[0021] Furthermore, the crushed stone is continuously graded in the range of 5-25 mm.

[0022] Furthermore, the fine beads are solid spherical, with continuous particle size distribution, and the median particle size of the laser particle size is 5.5 mm.

[0023] Furthermore, the steel fiber is a fine copper-plated steel fiber with a diameter of 0.15-0.25 mm, a length of 12-14 mm, an aspect ratio of 60-70, and a tensile strength of 2800-3200 MPa.

[0024] Furthermore, the PE fiber has a diameter of 11 to 13 μm, a length of 6 to 10 mm, an aspect ratio of 650 to 680, and a tensile strength of 2750 to 2850 MPa.

[0025] Furthermore, the thickness of the outer layer material is 60-200 mm, the thickness of the middle layer material is 50-150 mm, and the thickness of the inner layer material is 80-200 mm.

[0026] In a second aspect, the present invention provides a method for preparing a damage-resistant, high-insulation, fast-building composite material, comprising the following steps:

[0027] (1) weighing raw material components except water according to the mix ratio of magnesium phosphate cement-based high-strength concrete, adding them into a mixer and mixing them evenly to obtain a mixed dry material, then adding water and stirring to obtain a mixed slurry, and pouring it into a mold to form the inner layer material;

[0028] (2) weighing heavy-burned magnesium oxide, potassium dihydrogen phosphate, PE fiber and river sand according to the ratio of magnesium phosphate cement-based foamed concrete, adding them into the mixer, stirring them evenly to obtain a mixed dry material, then adding a mixed solution of sodium carbonate, sodium bicarbonate and water, stirring them evenly to obtain a mixed slurry, and directly pouring it on the inner layer material to form the middle layer material;

[0029] (3) Finally, according to the ratio of magnesium phosphate cement-based ultra-high performance concrete, heavy-burned magnesium oxide, potassium dihydrogen phosphate, borax, fine beads, steel fiber and river sand are weighed and added into a mixer, and mixed thoroughly to obtain a mixed dry material, and then water is added to the mixed dry material and mixed to obtain a mixed slurry, which is directly poured on the middle layer material to form the outer layer material.

[0030] The composite material consists of three layers: the outer layer is magnesium phosphate cement-based ultra-high performance concrete, which improves the density of the matrix by adopting a low water-cement ratio and adding fine beads. In addition, by adding steel fibers, the toughness of the concrete is improved, so that the outer layer has ultra-high strength and high toughness characteristics, ensuring the high anti-penetration performance of the composite material; the inner layer is magnesium phosphate cement-based foamed concrete, which introduces pores into the matrix by adding sodium carbonate and sodium bicarbonate to improve the energy absorption characteristics of the concrete, thereby ensuring the high explosion resistance and high thermal insulation performance of the composite material; the inner layer is magnesium phosphate cement-based high-strength concrete, as a structural layer. In addition, the cementitious material is mainly magnesium phosphate cement, which ensures the rapid construction of the composite material. The above functional layers are superimposed and combined to solve the problem that the existing concrete materials are difficult to coordinate in terms of anti-penetration, anti-explosion, thermal insulation and rapid construction. DETAILED DESCRIPTION

[0031] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0032] In the following examples, the raw materials used are required as follows:

[0033] Dead-burned magnesium oxide was purchased from Haicheng Qunli Mining Co., Ltd. in Liaoning Province. It was obtained by melting and calcining magnesite powder at a high temperature above 1500°C, and the particle size was mainly distributed in the range of 10-100 μm.

[0034] Potassium dihydrogen phosphate is chemically pure KH 2 PO 4 .

[0035] Borax is chemical analysis grade Na 2 B 4 O 7 10H 2 O.

[0036] The particle size of river sand is 0-5mm.

[0037] The crushed stone is continuously graded from 5 to 25 mm.

[0038] Fine beads are solid spherical, with continuous particle size distribution and ultra-fine. The median particle size of laser particle size is 5.5mm, and the oxide composition is mainly SiO 2 、Al2 O 3 and CaO, etc., were purchased from Shenzhen Dote Technology Co., Ltd.

[0039] The steel fiber is a fine copper-plated steel fiber with a diameter of about 0.2 mm, a length of about 13 mm, an aspect ratio of about 65, and a tensile strength of about 3000 MPa.

[0040] The PE fiber has a diameter of about 12 μm, a length of about 8 mm, an aspect ratio of about 666, and a tensile strength of about 2790 MPa.

[0041] Sodium carbonate is chemical analysis pure Na 2 CO 3 .

[0042] Sodium bicarbonate is chemically pure NaHCO 3 .

[0043] The water is tap water, which meets the requirements of Standard for Water Use in Concrete (JGJ63-2006).

[0044] The mixer is a single-shaft mixer.

[0045] The rest of the raw materials or processing techniques, unless otherwise specified, are conventional commercially available raw materials or conventional processing techniques in the art.

[0046] Example 1

[0047] A damage-resistant, high-heat-insulating, fast-building composite material, comprising the following components by weight:

[0048] Inner layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 30 parts of borax, 800 parts of river sand, 800 parts of crushed stone, and 360 parts of water;

[0049] Middle layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 2 parts of PE fiber, 500 parts of river sand, 20 parts of sodium carbonate, 15 parts of sodium bicarbonate, 600 parts of water;

[0050] Outer layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 18 parts of borax, 163 parts of fine beads, 150 parts of steel fiber, 1690 parts of river sand, and 215 parts of water.

[0051] Preparation method:

[0052] (1) Weighed dead-burned magnesium oxide, potassium dihydrogen phosphate, borax, river sand, and crushed stone are added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Water is then added to the mixed dry material and stirred for 2 minutes to obtain a mixed slurry. The slurry is poured into a mold with a size of φ500×240 mm to form an inner layer of a composite material with a pouring thickness of 80 mm, i.e., magnesium phosphate cement-based high-strength concrete.

[0053] (2) Weighed heavy-burned magnesium oxide, potassium dihydrogen phosphate, PE fiber and river sand were added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. A mixed solution of sodium carbonate, sodium bicarbonate and water was then added to the mixed dry material and stirred for 1 minute to obtain a mixed slurry, which was directly poured onto the magnesium phosphate cement-based high-strength concrete to form an intermediate layer of the composite material with a pouring thickness of 80 mm, namely, magnesium phosphate cement-based foamed concrete.

[0054] (3) Weighed heavy-burned magnesium oxide, potassium dihydrogen phosphate, borax, fine beads, steel fiber and river sand are added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Water is then added to the mixed dry material and stirred for 2 minutes to obtain a mixed slurry, which is directly poured onto the magnesium phosphate cement-based foamed concrete to form an outer layer of the composite material with a pouring thickness of 80 mm, i.e., magnesium phosphate cement-based ultra-high performance concrete.

[0055] (4) After the composite material hardens, it can be demoulded to obtain a damage-resistant, high-insulation, rapid construction material.

[0056] Example 2

[0057] A damage-resistant, high-heat-insulating, fast-building composite material, comprising the following components by weight:

[0058] Inner layer materials: 660 parts of dead-burned magnesium oxide, 420 parts of potassium dihydrogen phosphate, 18 parts of borax, 600 parts of river sand, 800 parts of crushed stone, and 360 parts of water;

[0059] Middle layer materials: 750 parts of dead-burned magnesium oxide, 660 parts of potassium dihydrogen phosphate, 2.3 parts of PE fiber, 400 parts of river sand, 18 parts of sodium carbonate, 18 parts of sodium bicarbonate, 700 parts of water;

[0060] Outer layer materials: 800 parts of dead-burned magnesium oxide, 700 parts of potassium dihydrogen phosphate, 20 parts of borax, 240 parts of fine beads, 150 parts of steel fiber, 1690 parts of river sand, and 200 parts of water.

[0061] Preparation method:

[0062] (1) Weighed dead-burned magnesium oxide, potassium dihydrogen phosphate, borax, river sand, and crushed stone are added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Water is then added to the mixed dry material and stirred for 2 minutes to obtain a mixed slurry. The slurry is poured into a mold with a size of φ500×240 mm to form an inner layer of a composite material with a pouring thickness of 80 mm, i.e., magnesium phosphate cement-based high-strength concrete.

[0063] (2) Weighed heavy-burned magnesium oxide, potassium dihydrogen phosphate, PE fiber and river sand were added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. A mixed solution of sodium carbonate, sodium bicarbonate and water was then added to the mixed dry material and stirred for 1 minute to obtain a mixed slurry, which was directly poured onto the magnesium phosphate cement-based high-strength concrete to form an intermediate layer of the composite material with a pouring thickness of 80 mm, namely, magnesium phosphate cement-based foamed concrete.

[0064] (3) Weighed heavy-burned magnesium oxide, potassium dihydrogen phosphate, borax, fine beads, steel fiber and river sand are added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Water is then added to the mixed dry material and stirred for 2 minutes to obtain a mixed slurry, which is directly poured onto the magnesium phosphate cement-based foamed concrete to form an outer layer of the composite material with a pouring thickness of 80 mm, i.e., magnesium phosphate cement-based ultra-high performance concrete.

[0065] (4) After the composite material hardens, it can be demoulded to obtain a damage-resistant, high-insulation, rapid construction material.

[0066] Example 3

[0067] A damage-resistant, high-heat-insulating, fast-building composite material, comprising the following components by weight:

[0068] Inner layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 30 parts of borax, 800 parts of river sand, 800 parts of crushed stone, and 360 parts of water;

[0069] Middle layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 2 parts of PE fiber, 500 parts of river sand, 20 parts of sodium carbonate, 15 parts of sodium bicarbonate, 600 parts of water;

[0070] Outer layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 18 parts of borax, 163 parts of fine beads, 150 parts of steel fiber, 1690 parts of river sand, and 215 parts of water.

[0071] Preparation method:

[0072] (1) Weighed dead-burned magnesium oxide, potassium dihydrogen phosphate, borax, river sand, and crushed stone are added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Water is then added to the mixed dry material and stirred for 2 minutes to obtain a mixed slurry. The slurry is poured into a mold with a size of φ500×240 mm to form an inner layer of a composite material with a pouring thickness of 100 mm, i.e., magnesium phosphate cement-based high-strength concrete.

[0073] (2) Weighed heavy-burned magnesium oxide, potassium dihydrogen phosphate, PE fiber and river sand were added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. A mixed solution of sodium carbonate, sodium bicarbonate and water was then added to the mixed dry material and stirred for 1 minute to obtain a mixed slurry, which was directly poured onto the magnesium phosphate cement-based high-strength concrete to form an intermediate layer of the composite material with a pouring thickness of 40 mm, namely, magnesium phosphate cement-based foamed concrete.

[0074] (3) The weighed heavy-burned magnesium oxide, potassium dihydrogen phosphate, borax, fine beads, steel fiber and river sand were added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Water was then added to the mixed dry material and stirred for 2 minutes to obtain a mixed slurry, which was directly poured onto the magnesium phosphate cement-based foamed concrete to form an outer layer of the composite material with a pouring thickness of 100 mm, i.e., magnesium phosphate cement-based ultra-high performance concrete.

[0075] (4) After the composite material hardens, it can be demoulded to obtain a damage-resistant, high-insulation, rapid construction material.

[0076] Example 4

[0077] A damage-resistant, high-heat-insulating, fast-building composite material, comprising the following components by weight:

[0078] Inner layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 30 parts of borax, 800 parts of river sand, 800 parts of crushed stone, and 360 parts of water;

[0079] Middle layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 2 parts of PE fiber, 500 parts of river sand, 20 parts of sodium carbonate, 15 parts of sodium bicarbonate, 600 parts of water;

[0080] Outer layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 18 parts of borax, 163 parts of fine beads, 150 parts of steel fiber, 1690 parts of river sand, and 215 parts of water.

[0081] Preparation method:

[0082] (1) Weighed dead-burned magnesium oxide, potassium dihydrogen phosphate, borax, river sand, and crushed stone are added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Water is then added to the mixed dry material and stirred for 2 minutes to obtain a mixed slurry. The slurry is poured into a mold with a size of φ500×240 mm to form an inner layer of a composite material with a pouring thickness of 30 mm, i.e., magnesium phosphate cement-based high-strength concrete.

[0083] (2) Weighed heavy-burned magnesium oxide, potassium dihydrogen phosphate, PE fiber and river sand were added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. A mixed solution of sodium carbonate, sodium bicarbonate and water was then added to the mixed dry material and stirred for 1 minute to obtain a mixed slurry, which was directly poured onto the magnesium phosphate cement-based high-strength concrete to form an intermediate layer of the composite material with a pouring thickness of 40 mm, namely, magnesium phosphate cement-based foamed concrete.

[0084] (3) Weighed heavy-burned magnesium oxide, potassium dihydrogen phosphate, borax, fine beads, steel fiber and river sand were added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Water was then added to the mixed dry material and stirred for 2 minutes to obtain a mixed slurry, which was directly poured onto the magnesium phosphate cement-based foamed concrete to form an outer layer of the composite material with a pouring thickness of 170 mm, i.e., magnesium phosphate cement-based ultra-high performance concrete.

[0085] (4) After the composite material hardens, it can be demoulded to obtain a damage-resistant, high-insulation, rapid construction material.

[0086] Example 5

[0087] A damage-resistant, high-heat-insulating, fast-building composite material, comprising the following components by weight:

[0088] Inner layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 30 parts of borax, 800 parts of river sand, 800 parts of crushed stone, and 360 parts of water;

[0089] Middle layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 2 parts of PE fiber, 500 parts of river sand, 20 parts of sodium carbonate, 15 parts of sodium bicarbonate, 600 parts of water;

[0090] Outer layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 18 parts of borax, 163 parts of fine beads, 150 parts of steel fiber, 1690 parts of river sand, and 215 parts of water.

[0091] Preparation method:

[0092] (1) Weighed dead-burned magnesium oxide, potassium dihydrogen phosphate, borax, river sand, and crushed stone are added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Water is then added to the mixed dry material and stirred for 2 minutes to obtain a mixed slurry. The slurry is poured into a mold with a size of φ500×240 mm to form an inner layer of a composite material with a pouring thickness of 80 mm, i.e., magnesium phosphate cement-based high-strength concrete.

[0093] (2) Weighed heavy-burned magnesium oxide, potassium dihydrogen phosphate, PE fiber and river sand were added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. A mixed solution of sodium carbonate, sodium bicarbonate and water was then added to the mixed dry material and stirred for 1 minute to obtain a mixed slurry, which was directly poured onto magnesium phosphate cement-based high-strength concrete to form an intermediate layer of a composite material with a pouring thickness of 120 mm, namely magnesium phosphate cement-based foamed concrete.

[0094] (3) Weighed heavy-burned magnesium oxide, potassium dihydrogen phosphate, borax, fine beads, steel fiber and river sand were added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Water was then added to the mixed dry material and stirred for 2 minutes to obtain a mixed slurry, which was directly poured onto the magnesium phosphate cement-based foamed concrete to form an outer layer of the composite material with a pouring thickness of 40 mm, i.e., magnesium phosphate cement-based ultra-high performance concrete.

[0095] (4) After the composite material hardens, it can be demoulded to obtain a damage-resistant, high-insulation, rapid construction material.

[0096] Comparative Example 1:

[0097] The composite material is prepared by using an ordinary silicate cement system. The thickness of the outer layer, the middle layer and the inner layer are the same as those in Example 1. The composite material includes the following components by weight:

[0098] Inner layer materials: 100 parts of PII·52.5 grade ordinary Portland cement, 1000 parts of river sand, 800 parts of crushed stone, 450 parts of water;

[0099] Middle layer materials: 1000 parts of PII·52.5 grade ordinary Portland cement, 2.5 parts of PE fiber, 1500 parts of river sand, 5 parts of composite foaming agent produced by Teshengqian New Building Materials Co., Ltd. (purchased from https: / / www.taobao.com / list / item / wap / 581873402493.htm), 400 parts of water;

[0100] Outer layer materials: 700 parts of PII·52.5 grade ordinary Portland cement, 300 parts of fine sinking beads, 100 parts of steel fiber, 1500 parts of river sand, 200 parts of water, and 20 parts of polycarboxylic acid high-efficiency water reducing agent.

[0101] Preparation method:

[0102] (1) Weighed PII·52.5 grade ordinary Portland cement, river sand, and crushed stone were added to a mixer in sequence and stirred for 3 min to obtain a mixed dry material. Water was then added to the mixed dry material and stirred for 2 min to obtain a mixed slurry. The slurry was poured into a mold with a size of φ500×240 mm to form an inner layer of the composite material. The pouring thickness was 80 mm.

[0103] (2) The foaming agent is diluted with water and foam is prepared in advance. The weighed PII·52.5 grade ordinary Portland cement, PE fiber and river sand are added to the mixer in turn and stirred for 3 minutes to obtain a mixed dry material. Water is then added to the mixed dry material and stirred for 1 minute to obtain a mixed slurry. The prefabricated foam is added to the mixed slurry and stirred evenly. The mixed slurry is directly poured on the inner layer of concrete to form a middle layer of the composite material. The pouring thickness is 80 mm.

[0104] (3) The weighed PII·52.5 grade ordinary Portland cement, potassium dihydrogen phosphate, borax, fine beads, steel fiber and river sand were added to the mixer in sequence and stirred for 3 min to obtain a mixed dry material. Subsequently, a mixture of water and polycarboxylic acid high-efficiency water reducer was added to the mixed dry material and stirred for 2 min to obtain a mixed slurry, which was directly poured onto the middle layer of concrete to form the outer layer of the composite material with a pouring thickness of 80 mm.

[0105] (4) After the composite material hardens, demoulding is possible.

[0106] Comparative Example 2

[0107] Magnesium phosphate cement-based high-strength concrete is used, including the following components: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 30 parts of borax, 800 parts of river sand, 800 parts of crushed stone, and 360 parts of water.

[0108] Preparation method:

[0109] (1) Weighed dead-burned magnesium oxide, potassium dihydrogen phosphate, borax, river sand, and crushed stone are added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Water is then added to the mixed dry material and stirred for 2 minutes to obtain a mixed slurry, which is then poured into a mold with a size of φ500×240 mm.

[0110] (2) After the composite material hardens, it can be demoulded.

[0111] Comparative Example 3

[0112] The magnesium phosphate cement-based foamed concrete comprises the following components by weight: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 2 parts of PE fiber, 500 parts of river sand, 20 parts of sodium carbonate, 15 parts of sodium bicarbonate and 600 parts of water.

[0113] Preparation method:

[0114] (1) Weighed dead-burned magnesium oxide, potassium dihydrogen phosphate, PE fiber and river sand were added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. A mixture of sodium carbonate, sodium bicarbonate and water was then added to the mixed dry material and stirred for 1 minute to obtain a mixed slurry, which was directly poured into a mold with a size of φ500×240 mm.

[0115] (2) After the composite material hardens, it can be demoulded.

[0116] Comparative Example 4

[0117] The magnesium phosphate cement-based ultra-high performance concrete includes the following components by weight: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 18 parts of borax, 163 parts of fine sedimentation beads, 150 parts of steel fibers, 1690 parts of river sand, and 215 parts of water.

[0118] Preparation method:

[0119] (1) Add the weighed dead-burned magnesium oxide, potassium dihydrogen phosphate, borax, fine beads, steel fiber and river sand into a mixer in turn, stir for 3 minutes to obtain a mixed dry material, then add water to the mixed dry material and stir for 2 minutes to obtain a mixed slurry, which is directly poured into a mold with a size of φ500×240 mm.

[0120] (2) After the composite material hardens, it can be demoulded.

[0121] Comparative Example 5

[0122] Inner layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 30 parts of borax, 800 parts of river sand, 800 parts of crushed stone, and 360 parts of water;

[0123] Middle layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 2 parts of PE fiber, 500 parts of river sand, 20 parts of sodium carbonate, 15 parts of sodium bicarbonate, 600 parts of water;

[0124] Outer layer material: The composition is the same as that of the inner layer material.

[0125] Preparation method:

[0126] (1) Weighed dead-burned magnesium oxide, potassium dihydrogen phosphate, borax, river sand, and crushed stone were added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Water was then added to the mixed dry material and stirred for 2 minutes to obtain a mixed slurry. The slurry was poured into a mold with a size of φ500×240 mm to form an inner layer of the composite material, and the pouring thickness was 80 mm.

[0127] (2) The weighed dead-burned magnesium oxide, potassium dihydrogen phosphate, PE fiber and river sand were added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Subsequently, a mixture of sodium carbonate, sodium bicarbonate and water was added to the mixed dry material and stirred for 1 minute to obtain a mixed slurry, which was directly poured onto the magnesium phosphate cement-based high-strength concrete to form an intermediate layer of the composite material with a pouring thickness of 80 mm.

[0128] (3) Weighed dead-burned magnesium oxide, potassium dihydrogen phosphate, borax, river sand, and crushed stone were added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Water was then added to the mixed dry material and stirred for 2 minutes to obtain a mixed slurry, which was directly poured onto the magnesium phosphate cement-based foamed concrete to form an outer layer of the composite material with a pouring thickness of 80 mm.

[0129] (4) After the composite material hardens, it can be demoulded.

[0130] Comparative Example 6

[0131] Outer layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 30 parts of borax, 800 parts of river sand, 800 parts of crushed stone, and 360 parts of water;

[0132] Inner layer material: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 2 parts of PE fiber, 500 parts of river sand, 20 parts of sodium carbonate, 15 parts of sodium bicarbonate, 600 parts of water;

[0133] Preparation method:

[0134] (1) Weighed dead-burned magnesium oxide, potassium dihydrogen phosphate, PE fiber and river sand were added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. A mixed solution of sodium carbonate, sodium bicarbonate and water was then added to the mixed dry material and stirred for 1 minute to obtain a mixed slurry, which was poured into a mold with a size of φ500×240 mm to form an inner layer of the composite material with a pouring thickness of 120 mm.

[0135] (2) Weighed dead-burned magnesium oxide, potassium dihydrogen phosphate, borax, river sand, and crushed stone are added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Water is then added to the mixed dry material and stirred for 2 minutes to obtain a mixed slurry. The slurry is poured on the inner layer material to form an outer layer of the composite material. The pouring thickness is 120 mm.

[0136] (4) After the composite material hardens, it can be demoulded.

[0137] Comparative Example 7

[0138] Inner layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 30 parts of borax, 800 parts of river sand, 800 parts of crushed stone, and 360 parts of water;

[0139] Middle layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 2 parts of PE fiber, 500 parts of river sand, 20 parts of sodium carbonate, 15 parts of sodium bicarbonate, 600 parts of water;

[0140] Outer layer materials: 880 parts of dead-burned magnesium oxide, 750 parts of potassium dihydrogen phosphate, 18 parts of borax, 1690 parts of river sand, and 215 parts of water.

[0141] Preparation method:

[0142] (1) Weighed dead-burned magnesium oxide, potassium dihydrogen phosphate, borax, river sand, and crushed stone were added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Water was then added to the mixed dry material and stirred for 2 minutes to obtain a mixed slurry. The slurry was poured into a mold with a size of φ500×240 mm to form an inner layer of the composite material, and the pouring thickness was 80 mm.

[0143] (2) The weighed dead-burned magnesium oxide, potassium dihydrogen phosphate, PE fiber and river sand were added to a mixer in sequence and stirred for 3 minutes to obtain a mixed dry material. Subsequently, a mixture of sodium carbonate, sodium bicarbonate and water was added to the mixed dry material and stirred for 1 minute to obtain a mixed slurry, which was directly poured onto the inner layer material to form a middle layer of the composite material with a pouring thickness of 80 mm.

[0144] (3) Add the weighed dead-burned magnesium oxide, potassium dihydrogen phosphate, borax and river sand into a mixer in turn and stir for 3 minutes to obtain a mixed dry material. Then, add water to the mixed dry material and stir for 2 minutes to obtain a mixed slurry, which is directly poured onto the middle layer material to form an outer layer of the composite material with a pouring thickness of 80 mm.

[0145] (4) After the composite material hardens, it can be demoulded.

[0146] Performance testing:

[0147] The concrete of the above-mentioned embodiments 1, 2, 3, 4, 5 and comparative examples 1, 2, 3, 4, 5, 6, 7 were tested. The method for determining the setting time of concrete refers to GB / T 50080-2016, and the method for determining the thermal conductivity refers to GB / T10294-2008. In addition, the target made of concrete was subjected to anti-penetration and anti-explosion tests respectively. The penetration test used a scaled-down earth-penetrating bomb, the material of the bomb was DT300 high-strength alloy steel, the diameter of the bomb was 25 mm, the aspect ratio of the bomb was 6, and the speed of the bomb was set to 200 m / s, ensuring that the impact surface of the target was perpendicular to the horizontal plane, and the center of the impact surface of the target was aligned with the center of the muzzle to ensure that the bomb could vertically enter the target at the center of the bull's eye; for the anti-explosion test, 1.0 kg TNT was used, the explosion mode was contact explosion, the explosive was placed in the center of the target surface, and all the explosives were effective charges. After the test was completed, the concrete penetration depth and the diameter of the explosion crater were measured with a steel ruler, and the results are shown in Table 1.

[0148] Table 1 Test results

[0149]

[0150] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A damage-resistant, high-heat-insulating, fast-building composite material, characterized in that: It includes an outer layer material, an intermediate layer material and an inner layer material which are compounded in sequence, wherein the outer layer material is made of magnesium phosphate cement-based ultra-high performance concrete, the intermediate layer material is made of magnesium phosphate cement-based foamed concrete, and the inner layer material is made of magnesium phosphate cement-based high-strength concrete, wherein: The magnesium phosphate cement-based ultra-high performance concrete comprises the following raw material components in parts by weight: Dead-burned magnesium oxide 500-1100 parts, potassium dihydrogen phosphate 400-900 parts, borax 9-25 parts, fine beads 110-210 parts, steel fiber 50-220 parts, river sand 1000-2000 parts, water 180-250 parts; The magnesium phosphate cement-based foamed concrete comprises the following raw material components in parts by weight: Dead-burned magnesium oxide 500-1100 parts, potassium dihydrogen phosphate 400-900 parts, sodium carbonate 5-50 parts, sodium bicarbonate 5-50 parts, PE fiber 0.5-3 parts, river sand 100-650 parts, water 400-800 parts; The magnesium phosphate cement-based high-strength concrete comprises the following raw material components in parts by weight: 500-1100 parts of dead-burned magnesium oxide, 400-900 parts of potassium dihydrogen phosphate, 15-45 parts of borax, 600-1200 parts of river sand, 600-1200 parts of crushed stone, and 300-500 parts of water.

2. The damage-resistant, high-heat-insulating, fast-building composite material according to claim 1, characterized in that: The dead-burned magnesium oxide is obtained by melting and calcining magnesite powder at a high temperature above 1500°C.

3. The damage-resistant, high-heat-insulating, fast-building composite material according to claim 1, characterized in that: The potassium dihydrogen phosphate is chemical analysis pure KH2PO4; The borax is chemical analysis pure Na2B4O7·10H2O; The sodium carbonate is chemical analysis pure Na2CO3; The sodium bicarbonate is chemical analysis pure NaHCO3.

4. The damage-resistant, high-heat-insulating, fast-building composite material according to claim 1, characterized in that: The particle size of the river sand is 0-5mm, and is not equal to 0.

5. The damage-resistant, high-heat-insulating, fast-building composite material according to claim 1, characterized in that: The crushed stone is of continuous gradation of 5-25 mm.

6. The damage-resistant, high-heat-insulating, fast-building composite material according to claim 1, characterized in that: The fine beads are solid spherical in shape, with continuous particle size distribution, and the median particle size of the laser particle size is 5.5 mm.

7. The damage-resistant, high-heat-insulating, fast-building composite material according to claim 1, characterized in that: The steel fiber is a fine copper-plated steel fiber with a diameter of 0.15-0.25 mm, a length of 12-14 mm, an aspect ratio of 60-70, and a tensile strength of 2800-3200 MPa.

8. The damage-resistant, high-heat-insulating, fast-building composite material according to claim 1, characterized in that: The PE fiber has a diameter of 11 to 13 μm, a length of 6 to 10 mm, an aspect ratio of 650 to 680, and a tensile strength of 2750 to 2850 MPa.

9. The damage-resistant, high-heat-insulating, fast-building composite material according to claim 1, characterized in that: The thickness of the outer layer material is 60-200 mm, the thickness of the middle layer material is 50-150 mm, and the thickness of the inner layer material is 80-200 mm.

10. The method for preparing the damage-resistant, high-heat-insulating, fast-building composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) weighing raw material components except water according to the mix ratio of magnesium phosphate cement-based high-strength concrete, adding them into a mixer and mixing them evenly to obtain a mixed dry material, then adding water and stirring to obtain a mixed slurry, and pouring it into a mold to form the inner layer material; (2) weighing heavy-burned magnesium oxide, potassium dihydrogen phosphate, PE fiber and river sand according to the ratio of magnesium phosphate cement-based foamed concrete, adding them into the mixer, stirring them evenly to obtain a mixed dry material, then adding a mixed solution of sodium carbonate, sodium bicarbonate and water, stirring them evenly to obtain a mixed slurry, and directly pouring it on the inner layer material to form the middle layer material; (3) Finally, according to the ratio of magnesium phosphate cement-based ultra-high performance concrete, heavy-burned magnesium oxide, potassium dihydrogen phosphate, borax, fine beads, steel fiber and river sand are weighed and added into a mixer, and mixed thoroughly to obtain a mixed dry material, and then water is added to the mixed dry material and mixed to obtain a mixed slurry, which is directly poured on the middle layer material to form the outer layer material.

Citation Information

Patent Citations

  • Magnesium phosphate cement for emergency repair and rushing construction under cold environments and preparation method thereof

    CN108191276A

  • Heat insulation and protection integrated composite wall and preparation method thereof

    CN110066188A